2014
DOI: 10.5194/hessd-11-10043-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Derivation of a new continuous adjustment function for correcting wind-induced loss of solid precipitation: results of a Norwegian field study

Abstract: Abstract. Precipitation measurements exhibit large cold-season biases due to under-catch in windy conditions. These uncertainties affect water balance calculations, snowpack monitoring and calibrations of remote sensing algorithms and land surface models. More accurate data would improve the ability to predict future changes in water resources and mountain hazards in snow-dominated regions. In 2010, an extensive test-site for precipitation measurements was established at a mountain plateau in Southern Norway.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 14 publications
2
59
0
1
Order By: Relevance
“…Underestimation of ∼20%–30% of total precipitation is typical for tipping‐bucket precipitation gauges, with wind‐induced undercatch the major source of error [ Villarini et al , ]. For solid precipitation, Wolff et al [] found a nonlinear relationship between wind speed and undercatch, with strong temperature dependence. There is also undercatch caused by evaporation and sublimation [ Rasmussen et al , ].…”
Section: Databasementioning
confidence: 99%
“…Underestimation of ∼20%–30% of total precipitation is typical for tipping‐bucket precipitation gauges, with wind‐induced undercatch the major source of error [ Villarini et al , ]. For solid precipitation, Wolff et al [] found a nonlinear relationship between wind speed and undercatch, with strong temperature dependence. There is also undercatch caused by evaporation and sublimation [ Rasmussen et al , ].…”
Section: Databasementioning
confidence: 99%
“…measurements have been the subject of many studies (e.g., Alter 1937;Sevruk and Klemm 1989;Sevruk et al 1991;Larson 1993;Yang et al 1993;Goodison et al 1998;Sugiura et al 2003Sugiura et al , 2006, there have been only a limited number of coordinated assessments of the accuracy, reliability, and repeatability of automatic precipitation measurements (e.g., Tumbusch 2003;Duchon 2008;Smith 2009;Rasmussen et al 2012;Savina et al 2012;Wolff et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is comparable to the results found in Thériault et al (2012). Wolff et al (2014) found nonlinear mathematical relationships between collection efficiency and wind speed based on dry snow, mixed precipitation, and rain measurements made at the Haukeliseter (Norway) field site. In this work, a sigmoid law has been adopted to fit the simulated CE values for different particle size distributions in the following form:…”
mentioning
confidence: 99%
“…Another question is whether the low skill for m for Bjørnholt in winter can be attributed to more snow and less liquid rain, for instance under-catch (Wolff et al, 2014). Another explanation is that low values of m during winter means that the calibration with its annually aggregated value emphasises the warmer seasons with typically higher values.…”
Section: Discussionmentioning
confidence: 90%